Joining processes of CFRP‐Al sheets in automobile lightweighting technologies: A review. Issue 12 (10th October 2022) - Han, Shanling; Guang, Xinjie; Li, Zhiyong; Li, Yong
Abstract: According to the development trend of modern car body, the future car body will be composed of steel, aluminum‐magnesium alloy, plastic, carbon fiber reinforced polymer (CFRP), and other lightweight materials. Hybrid material body represents the latest development trend of car body structure in the future. With the development of lightweight technology, the application of carbon fiber composite material in automobile bodies is increasing due to its exceptional performance. Therefore, the joining of carbon fiber sheets with dissimilar sheets process in the hybrid material body is a key technical problem that needs to be solved. In this paper, the existing joining processes of adhesive process, mechanical joining, welding process, and hybrid joining for carbon fiber composites are reviewed; the principle, development, advantages, and shortcomings of each process for carbon fiber composites joining processes are systematically described; and the latest progress of the joining process are introduced. The purpose is tantamount to broaden the application range of carbon fiber sheets with dissimilar sheets and provide reference for its extensive application in the development of hybrid car body and lightweight. Abstract :